Pharmacological Heart Rate Lowering in Patients with a Preserved Ejection Fraction – Review of a Failing Concept - Meyer, Markus (Heart Fail Rev, 2018)
Epidemiological studies have demonstrated that high resting heart rates are associated with increased mortality. Clinical studies in patients with heart failure and reduced ejection fraction have shown that heart rate lowering with beta-blockers and ivabradine improves survival. It is therefore often assumed that heart rate lowering is beneficial in other patients as well. Here we critically appraise the effects of pharmacological heart rate lowering in patients with both normal and reduced ejection fraction with an emphasis on the effects of pharmacological heart rate lowering in hypertension and heart failure. Emerging evidence from recent clinical trials and meta-analyses suggest that pharmacological heart rate lowering is not beneficial in patients with a normal or preserved ejection fraction. This has just begun to be reflected in some but not all guideline recommendations. The detrimental effects of pharmacological heart rate lowering are due to an increase in central blood pressures, higher left ventricular systolic and diastolic pressures and increased ventricular wall stress. Therefore, we propose that heart rate lowering per se reproduces the hemodynamic effects of diastolic dysfunction and imposes an increased arterial load on the left ventricle, which combine to increase the risk of heart failure and atrial fibrillation. Pharmacologic heart rate lowering is clearly beneficial in patients with a dilated cardiomyopathy but not in patients with normal chamber dimensions and normal systolic function. These conflicting effects can be explained based on a model that considers the hemodynamic and ventricular structural effects of heart rate changes.